1999
DOI: 10.1111/j.1349-7006.1999.tb00691.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Anti‐tumor Activity of a Novel Indolocarbazole Compound, J‐107088, on Murine and Human Tumors Transplanted into Mice

Abstract: The ratio of LD 10 /GID 75 indicates the therapeutic window of an anti-tumor agent. Although the ratios of doxorubicin, paclitaxel and cisplatin against PC-3 were < < < <0.3, < < < <0.5 and < < < <0.2, J-107088 showed the widest therapeutic window among the anti-tumor drugs tested. J-107088 was also effective on cells that had acquired resistance related to P-glycoprotein. Furthermore, J-107088 was found to be highly effective in inhibiting proliferation of micro-metastases of tumors to the liver in mice. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 6 publications
2
27
0
Order By: Relevance
“…The results across all experiments confirmed the previously reported high margin of safety observed with edotecarin (17). In general, decreases in net body weight were comparable across treatments within a study and did not seem to differ significantly (Supplementary Table S8A).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The results across all experiments confirmed the previously reported high margin of safety observed with edotecarin (17). In general, decreases in net body weight were comparable across treatments within a study and did not seem to differ significantly (Supplementary Table S8A).…”
Section: Resultssupporting
confidence: 85%
“…The antitumor efficacy of edotecarin, when used as a single agent, has been characterized in vitro with human cancer cells and in vivo with human tumor models in nude mice (10,15,17). For example, cytotoxic activity against a panel of 31 human cancer cells has been shown, with IC 50 values ranging from 0.0015 to 0.39 Amol/L (10,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 To date, combinational treatment regimens that include PTX have been reported to be successful in targeting hormone-refractory prostate cancers in clinical trials 20 as well as in an animal study involving PC-3 xenograft models. 21 The principal mechanism of the cytotoxic action of PTX is stabilization of microtubules, which leads to mitotic arrest. 22 PTX has also been shown to have a potent inhibitory effect on angiogenesis, 23 a process that has been proposed as a target for the chemotherapeutic treatment of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[16] The activity of edotecarin was described by Arakawa et al in the same year, [17] and was shown to work by stabilising the DNA-topoisomerase I complex. This resulted in cells being incapable of unwinding DNA and therefore preventing them from dividing.…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%